Charge transfer in He+ + Li and He+ + Cd collisions* - Auciello, O. H.; Alonso, E. V.; Baragiola, R. A. (American Physical Society, 1976)
Fil: Auciello, O. H. Comisión Nacional de Energía Atómica; Argentina